Durable goods and ICT: The drivers of Euro area productivity growth? - Jukka Jalava; Ilja Kristian Kavonius (The Research Institute of the Finnish Economy (ETLA), 2008)
The purpose of this paper is to estimate the effect of durable goods and ICT on Euro Area economic growth and productivity change; when expenditure on consumer durables is recorded as capital investment. The capitalization of consumer durables impacts both the levels and growth rates of the capital stock, productivity and GDP. Our growth accounting computations demonstrated that the capital services of durables contributed one-tenth of economic growth and one-eight of labour productivity growth in 1995-2004. ICT's impacts were larger, i.e., one-fifth of GVA growth and one-sixth of labour productivity growth.
Keywords: E13; E21; E22; O11; O47; O52; 330; durable good; asset; productivity; ICT; growth accounting; capital services; household production; Dauerhaftes Konsumgut; Informationstechnik; Produktivität; Wirtschaftswachstum; Europäische Wirtschafts- und Währungsunion; EU-Staaten